Ramen : 80 easy noodle bowls and broths - Sano, Makiko (OH! Life, 2023)
With slurpable noodles, umami broths and colorful customizable toppings, this unique comfort food can be endlessly adapted according to your individual tastes and creativity. Learn the basics of broths and noodles, plus a range of add-ons to adapt as you like.